2010
DOI: 10.1051/0004-6361/200913394
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary determinations of the masses of the neutron star and mass donor in the high mass X-ray binary system EXO 1722–363

Abstract: Aims. We intended to measure the radial velocity curve of the supergiant companion to the eclipsing high mass X-ray binary pulsar EXO 1722-363 and hence determine the stellar masses of the components. Methods. We used a set of archival K s -band infrared spectra of the counterpart to EXO 1722-363 obtained using ISAAC on the VLT, and cross-correlated them in order to measure the radial velocity of the star. Results. The resulting radial velocity curve has a semi-amplitude of 24.5 ± 5.0 km s −1 . When combined w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The X-ray pulsar features a spin period of 413.89 s (with short time scale variability as large as 1µs/s) and a persistently high obscuration, with an absorbing column density varying along the orbit and averaging to 2 × 10 22 cm −2 Manousakis and Walter, 2011). Detailed hydrodynamic simulations of EXO 1722-363 indicated that its high obscuration is linked with the low velocity (∼ 500 km/s) of the companion stellar wind and constrained the neutron star mass to 1.75-2.15 (Manousakis et al, 2012b), a value slightly larger but compatible with the kinematic value of 1.5 ± 0.4 (Mason et al, 2010). IGR J17354-3255 was discovered with INTEGRAL in 2006 (Kuulkers et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The X-ray pulsar features a spin period of 413.89 s (with short time scale variability as large as 1µs/s) and a persistently high obscuration, with an absorbing column density varying along the orbit and averaging to 2 × 10 22 cm −2 Manousakis and Walter, 2011). Detailed hydrodynamic simulations of EXO 1722-363 indicated that its high obscuration is linked with the low velocity (∼ 500 km/s) of the companion stellar wind and constrained the neutron star mass to 1.75-2.15 (Manousakis et al, 2012b), a value slightly larger but compatible with the kinematic value of 1.5 ± 0.4 (Mason et al, 2010). IGR J17354-3255 was discovered with INTEGRAL in 2006 (Kuulkers et al, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…The source position was refined with INTEGRAL Walter et al, 2004) and further with XMM-Newton, which allowed an association with an infrared counterpart (Zurita . Its infrared spectrum was identified with that of a supergiant B0-B1Ia star, located at a distance of 7.1 − 7.9 kpc Mason et al, 2009Mason et al, , 2010. The orbital period of 9.742d, determined with RXTE (Markwardt and Swank, 2003;Corbet et al, 2005b) and refined with INTEGRAL thanks to the presence of X-ray eclipses, established the system as a sgHMXB.…”
Section: Discussionmentioning
confidence: 93%
“…Ground-based observations (Mason et al 2009(Mason et al , 2010 showed that the donor star is likely a B0-5I or B0-1 Ia. Optical and infrared (IR) observations confirmed the supergiant nature and showed prominent P-Cygni profile .…”
Section: Introductionmentioning
confidence: 94%
“…Input and output parameters for the MC simulations used to finally estimate the mass of the NSs hosted in the ten HMXBs. Mason et al (2011); (e) Quaintrell et al (2003); ( f ) Mason et al (2010), (g) Mason et al (2012); (h) Howarth et al (1997); (i) Zuiderwijk (1995); ( j) evaluated at periastron; (k) we used the same Ω as for SMC X-1 since the values of v rot sin i for these systems are compatible to within the uncertainties (see also Rawls et al 2011); (l) we assumed a value of K opt derived from the average of the other systems in this table with properties close to XTE J1855-026; (m) we assume a conservative Ω value to be close to the Roche lobe radius; ( * ) we treat 4U 1700-377 differently, since the project semi-major axis, a x sin i, is unknown; see Sect. 5.1.…”
Section: Masses Of the Ten Neutron Starsmentioning
confidence: 99%
“…The neutron star masses for LMC X-4, Cen X-3, 4U 1538-52, SMC X-1, and Vela X-1 are taken from Rawls et al (2011), while the mass of the neutron star hosted in 4U 1700-377 is derived from Clark et al (2002). The corresponding values for SAX J1802.7-2017, EXO 1722-363, and OAO 1657-415 are obtained from Mason et al (2011Mason et al ( , 2010Mason et al ( , 2012. We note that our estimated uncertainties on the neutron star masses are somewhat more conservative than those reported by Rawls et al (2011) and slightly smaller than those obtained by Clark et al (2002) and Mason et al (2011Mason et al ( , 2010Mason et al ( , 2012.…”
Section: Masses Of the Ten Neutron Starsmentioning
confidence: 99%